2012
DOI: 10.1515/jpm.2011.135
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal cord blood lipids in intrauterine growth restriction

Abstract: Our results support the hypothesis of a disturbed cholesterol supply in IUGR fetuses. Born SGA has been shown to be a risk factor for developing cardiovascular disease later in life. Since HDL-C has anti-inflammatory properties, a reduced HDL-C during fetal development, and an increase in atherogenic indices, might provide a link to this observation in IUGR fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 30 publications
5
72
1
1
Order By: Relevance
“…In our study, we observed that in serum HDL-Cholesterol in IUGR group was lower than those in a term AGA group, which was a statistically significant finding.This finding is similar with study conducted by Pecks U et al 19 Maternal cholesterol is actively transferred via the placenta. At the apical placental surface facing maternal blood, i.e., the syncytiotrophoblast, many lipoprotein receptors are involved in cholesterol uptake.…”
Section: Serum Hdl-cholesterolsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, we observed that in serum HDL-Cholesterol in IUGR group was lower than those in a term AGA group, which was a statistically significant finding.This finding is similar with study conducted by Pecks U et al 19 Maternal cholesterol is actively transferred via the placenta. At the apical placental surface facing maternal blood, i.e., the syncytiotrophoblast, many lipoprotein receptors are involved in cholesterol uptake.…”
Section: Serum Hdl-cholesterolsupporting
confidence: 93%
“…before the 6th month) fetal LDL correlates to LDL levels of the mothers, while in third trimester this correlation is virtually absent. 19 From above observation and from our study observation we can say that a basal LDL production rate is maintained by the fetus throughout gestation. Throughout pregnancy maternal LDL may contribute to the fetal LDL pool with decreasing amounts, until at term the LDL concentration reflects the basal production rate of the fetus.…”
Section: Serum Ldl-cholesterolsupporting
confidence: 64%
“…Conversely, increased TGs during pregnancy have been shown to augment the risk of preeclampsia, preterm birth, and fetal growth restriction (FGR) ( 2,5 ). The lipid metabolism and plasma levels are also affected by maternal factors such as body mass index (BMI), maternal weight gain, maternal nutrition, prepregnancy lipid levels, and various medical complications of pregnancy such as diabetes ( 6 ).…”
Section: Rna Extraction and Cdna Synthesismentioning
confidence: 99%
“…There is increasing evidence shown that an abnormal lipid profile during gestation may increase the risk of cardiovascular disease and result in undesirable outcomes for the mother and the fetus, including preeclampsia [7,8], gestational diabetes mellitus [9,10], intrauterine growth restriction and premature birth [11,12].…”
Section: Introductionmentioning
confidence: 99%